Modal Sosial Dalam Pengembangan Destinasi Wisata Kampung Bali di Kota Bekasi - Nissa, Zahratun; Sugiarti, Cucu; Rizki, Mochamad Faizal (Universitas Muhammadiyah Sumatera Utara, 2024)
Kampung Bali Tourism Destination in Bekasi City, since its establishment in 2020, has experienced rapid growth thanks to the community's dedication in promoting Balinese culture. With a cultural concept, this destination introduces local wisdom, art, and daily life of Balinese people in an urban environment. This research aims to evaluate the application of social capital in the management of Kampung Bali Bekasi Tourism Destination, which has gained regional and national recognition. The research method uses a phenomenological approach and refers to Robert D. Putnam's social capital theory, focusing on trust, networks, and norms. The results showed that Kampung Bali Bekasi Tourism Destination effectively utilizes social capital, especially in building and expanding networks (bonding and bridging), as well as strengthening norms rooted in the local community.Keywords: Tourism, Social Capital, Trust, Networks, Norms